Antigen retrieval immunohistochemistry based research and diagnostics - Shi, Shan-Rong, 1936-; Taylor, C. R. (Clive Roy) (New Jersey : Wiley, 2010)
'An antigen is a substance that prompts the generation of antibodies and can cause an immune response. The antigen retrieval (AR) technique is used worldwide and has resulted in a revolution in immunohistochemistry (IHC). Featuring contributors who are distinguished experts and researchers in the field, this book discusses several scientific approaches to the standardization of quantifiable IHC. It summarizes the key problems in the four fields of antigen retrieval and provides practical methods and protocols in AR-IHC. Clinical pathologists, molecular cell biologists, basic research scientists, technicians, and graduate students, will benefit from this fully up-to-date work'--
'This book is based on the development and application of AR by the editors, one of whom is the inventor of AR, together with members of a world-leading research center of AR'--
Keywords: Immunohistochemistry; Antigens